2019
DOI: 10.1115/1.4044685
|View full text |Cite
|
Sign up to set email alerts
|

A New Structural Bump Foil Model With Application From Start-Up to Full Operating Conditions

Abstract: This paper presents a new structural bump foil model that can handle all operating conditions from start-up to full speed. The model is based on a nonlinear contact algorithm with friction and gaps. The top foil is modeled as a curved beam while bump foil uses a coupled truss model. The model considers the gaps between the bump foil and the bearing casing, between the bump foil and the top foil and between the rotor and the top foil. Thus, any numerical interference between the rotor and the top foil is avoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The validation of the foil model in Figure 2, based on the displacement results of a cantilever beam in a uniform and a increasing load case (LC) by Le Lez et al [17], shows a good agreement. The present NDOF bump-foil model, established by Le Lez et al [17], is further extended by Arghir et al [18,19], which is not the scope of the present study.…”
Section: Bump-type Foil Air Bearing Modelmentioning
confidence: 87%
“…The validation of the foil model in Figure 2, based on the displacement results of a cantilever beam in a uniform and a increasing load case (LC) by Le Lez et al [17], shows a good agreement. The present NDOF bump-foil model, established by Le Lez et al [17], is further extended by Arghir et al [18,19], which is not the scope of the present study.…”
Section: Bump-type Foil Air Bearing Modelmentioning
confidence: 87%
“…Previous studies [10] suggested that the bearings' static characteristic results based on Heshmat's linear spring model [24] were instructive to the research based on the N DOF model [32,33]. Hence, these two analytical foil models were adopted in this paper to obtain the foil structure's local deformation u in equation (6), and the details are shown in figure 1(e).…”
Section: Expression Of Film Thickness Considering Textures and Misali...mentioning
confidence: 99%
“…Recently, Arghir and Benchekroun [25] further developed the foil model introduced in [17] by modeling the closeloose contacts between the top foil and the bump foil to consider possible gaps and manufacturing errors in the foil structure. This foil model was then coupled with the gas film model to determine all operating conditions of GFBs from start-up to full speed [26]. However, all of the above models are planar models, thus they cannot reflect the three-dimensional (3D) characteristics of a bump foil.…”
Section: Introductionmentioning
confidence: 99%